The Coral-Rich Devonian Limestones of the English Riviera UNESCO Global Geopark - Malcolm Hart; Christopher Smart (Geoconservation Research)
The coral-rich limestones of the English Riviera UNESCO Global Geopark were an important component of the original definition of the Devonian System, introduced by Sedgwick and Murchison in 1840. They are, therefore, both a local highlight of the geological succession but have an important position within the history of geology. Formed in the tropical seas of the Middle Devonian, 10°S of the Equator, they also demonstrate the history of Devon in terms of Continental Drift and Plate Tectonics. Caves in these limestones provide an important record of both marine and terrestrial Pleistocene history, including some important hominin remains.